THE IMPLEMENTATION OF WHISPERING GAME TECHNIQUE TO ENHANCE THE STUDENTS’ LISTENING SKILL - Nofriati, Eli; Mutia Rahmi (Journal of English Education and Social Science, 2023)
The research was conducted in Collaborative Classroom Action at SMA Negeri 3 Bireuen. The aims of the research are: 1). To know Whispering Game Technique can improve the students’ listening skill to the eleventh-grade students of SMA Negeri 3 Bireuen. 2). To investigate the students’ response toward the implementation of Whispering Game Technique in learning listening skill. The subject of the research was the eleventh-grade students of SMA Negeri 3 Bireuen. The research data was collected from observation checklist, listening test, questionnaire and field note. The data was analyzed in qualitative and qualitative research. The researcher found some research results. The first, the result findings from the students’ listening test in cycle one was 48.81 and became to 77.72 in cycle 2. The second result finding was found from the observation of the teacher’s performance was 60% in cycle I and increase to 80%. Meanwhile, the percentage of students’ activities in the first cycle was found 53% and increase to 75%. The third result finding found that the result of students’ response toward the implementation of Whispering Game Technique. Based on the result, the students gave good (positive response) about the technique. It could be seen from the category of questionnaire result showed that in “strongly agree” category or in level 3.78. From the results findings above, it could be concluded that Whispering Game Technique improves the students’ listening skill.